Perspectives on Water Usage for Biofuels Production Aquatic Contamination and Climate Change (Springer International Publishing, 2018)
The book integrates the fundamental factors that determine current and future impacts of biofuels production on water supply and demand in the context of climatic changes. The effects of biofuels production on ground water quality with increasing water scarcity are examined, and the utilization of water sources in the commercial scale production of biofuels are sketched, covering the complete route from growing of crops to biorefinery. Biofuel's chemical composition, characteristics and uses as fuel in terms of water consumption are also investigated. Overall, the diversity of biomass, various technological approaches and microbial contribution are reviewed. Learning objectives on this topic are presented by means of a series of tables and figures in order to guide both professionals and students. The present manuscript deals with biofuel and bioenergy courses and is therefore invaluable to students. The book provides thorough coverage of all industrial aspects of biofuels production, including impacts of climate change and water availability. It will play vital role for industry employees involved in product development, production management, quality management and helpful source to those studying for professional qualification. Academics involved in teaching elements of the subject and persons involved in an environment regulatory capacity would be able to take advantage from this book.